Implementasi Pembelajaran Bermakna di Madrasah untuk Meningkatkan Mutu Pendidikan Islam - Muhammad Yusran; Muhammad Nur Effendi; Hasan Hasan (STIT Syekh Muhammad Nafis Tabalong, 2026)
The quality of Islamic education in Madrasahs depends significantly on the effectiveness of the learning process, which must address students' cognitive, affective, and psychomotor domains. However, reality shows that the learning process often falls into rote learning patterns. This study aims to analyze the implementation strategy of meaningful learning as a systematic effort to improve the quality of education in Madrasahs. The research method employed is library research using content analysis of the literature related to David Ausubel's cognitive theory and educational quality management. The results show that the strategy for implementing meaningful learning involves using advanced organizers, progressive differentiation, integrative reconciliation, and the utilization of the